Analisis Evaluasi Penggunaan Teknologi dalam Pembelajaran Pendidikan Agama Islam: Studi Pustaka - Nia Saskia Ramadhani; Shobrun Jamil; M. Ulil Abshar Abdalla; Adinda Aulia Azahra (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
The advancement of digital technology today has had a significant influence on the world of education, including in the learning process of Islamic Religious Education (PAI). The use of technology in PAI learning is considered to help increase learning effectiveness and facilitate access to materials for students. However, the implementation of technology in learning still faces obstacles that affect the effectiveness of the use of technology. The purpose of this study is to analyze the evaluation of the use of technology in PAI learning through a literature review approach. This research uses a qualitative research method with literature study, namely through the collection of various journals, scientific articles, and reliable sources related to the use of technology in Islamic Religious Education learning. The results of the study show that the use of technology, such as learning videos, digital learning media, and online learning platforms, is able to design student participation, learning motivation, and help students understand learning materials. In addition, technology also makes it easier for teachers to deliver material in a more varied, interesting, and efficient manner. However, the success of the application of technology in PAI learning is still influenced by several factors, including the ability of teachers to use technology, the availability of supporting facilities, and the readiness of students to conduct technology-based learning. Therefore, it is necessary to evaluate and develop technology in PAI learning so that it runs optimally and in accordance with the goals of Islamic Education.